Pemanfaatan Kapur Sirih pada Pelunakan Kulit Kayu Kepuak sebagai Bahan Pakaian - Mangurai, Silvia Uthari Nuzaverra Mayang; Diba, Farah; Arbiastutie, Yanieta (Prima Abdika: Jurnal Pengabdian Masyarakat, 2024)
The kepuak bark clothing has been used by people in Kalimantan, especially the Dayak tribe. Kepuak bark clothing is one of the cultures of the community, including the people of Belaban Ella village. Kepuak bark clothing is only used on certain occasions because of its stiff and rough texture. The purpose of this service activity is to convey information regarding the benefits of whiting as a softening agent for kepuak bark in Belaban Ella Village, Menukung District, Melawi Regency. The service activity was attended by 31 participants. Monitoring and evaluation of activities in the form of questionnaires was carried out before and after the activity. The questionnaire results showed that the understanding community increased after deliver of the knowledge. The insight of community was enhanced by utilizing whiting to soften the kepuak bark for clothing. The use of kepuak can maintain community culture. Kepuak bark-whiting soaked has potential to be used as clothing that can be ysed daily because has softer texture, can improve the economy, and encourage the community to protect the forest by planting more kepuak trees.